Energy extraction from ocean currents using straight bladed cross-flow hydrokinetic turbine. Issue 1 (April 2017) - Dudhgaonkar, Prasad; Duraisamy, Nagasamy; Jalihal, Purnima
Harvesting marine renewable energy remains to be a prime focus of researchers across the globe both in environmental and in commercial perspectives. India is blessed with a long coastline, and the seas around Indian peninsula offer ample potential to tap various ocean energy forms. National Institute of Ocean Technology carries out research and various ocean energy technologies, out of which harnessing kinetic energy in seawater currents is one. This article presents the open sea trials recently carried out on National Institute of Ocean Technology's cross-flow hydrokinetic ocean current turbine in South Andaman. The turbine was designed to generate 100 W electricity at 1.2 m/s current speed and was built in-house. The turbine was initially tested in a seawater channel and then was deployed in Macpherson Strait in Andaman. It was fitted below a floating platform designed especially for this purpose, and the performance of the turbine was continuously logged inside an on-board data acquisition system. The trials were successful and in line with computations.